The Supply of Staple Foodstuffs to the Armed Forces in Nigeria during the Inter-War Years - Adeniyi, Oluwasegun Thaddaeus (NIU Journal of Humanities; Vol 10 No 1 (2025): NIU Journal of Humanities, Vol. 10 No. 1, March 2025, 2025)
This research explored the critical role of staple foodstuff supply in sustaining the Nigerian Armed Forces during the inter-war years (1919-1939). It investigated the challenges and strategies employed by the colonial government to ensure adequate provision of essential food items to troops stationed across the vast Nigerian territory. The study relied essentially on primary archival sources for its analysis. Files of the Central Secretary’s Office (CSO) on the colonial Nigeria war-economy and the armed forces deposited in the National Archives at Ibadan (NAI), Enugu and Kaduna provided the data for the historical analysis. The study of this phenomenon in West Africa will contribute towards a more global perspective of the history of the Great War. By examining factors such as agricultural production, transportation infrastructure, storage facilities, and procurement policies, the study threw light on the complex logistical operations involved in feeding the military during this period. Additionally, it analyzed the impact of food shortages, economic fluctuations, and global events on the supply chain and its consequences for the morale and effectiveness of the Nigerian Armed Forces. Keywords: Armed Forces, Strategy, Government, Infrastructure, Fluctuations.